Investigating the effect of N-terminal methionine addition, hydrophobic interaction enhancement and loop modification in modifying immunomodulatory and cancer-inhibitory activities of FIP-fve mutants - Chan, Won Ting (2019)
FIP-fve is an immunomodulatory protein isolated from edible enokitake mushroom Flammulina velutipes and grouped under fungal immunomodulatory proteins (FIPs) family. FIPs are well documented for their immunomodulation, anti-allergy and anti-tumour activities. Herein, this study is motivated by a lack of understanding in regard to structural and functional relationship of FIP-fve as well as other FIPs in the FIP family in association to immunomodulatory and cancer-inhibitory activities. The knowledge in structure-function paradigm may reveal fundational characteristics of FIP-fve in delivering its associated functions. The three-dimensional (3D) structure of FIP-fve is the first protein structure that is determined in FIPs family, by which it is also one of the most well delineated FIP structure. Examination to the structural data of FIP-fve revealed three important aspects that may be crucial in determining and/or enhancing its bioactivities. Firstly, it is hypothesized that reinforcing of hydrophobic interaction in N-terminal inter-helices via hydrophobic amino acid substitution would further improve its functional activities. Secondly, possible mutational benefits with addition of highly conserved N-terminal methionine in FIPs family to beginning of N-terminal of FIP-fve were investigated. Thirdly, it is believed that loops that connect beta-strands in FIP-fve are responsible in determining its bioactivities, and adoption of loops from Ling Zhi-8 (LZ-8), FIP from Ganoderma lucidum might strengthen bioactivities of FIP-fve. It is expected that LZ-8 that is isolated from medicinal mushroom Ganoderma lucidum possesses higher curative status in comparison to FIP-fve that is extracted from cuisine mushroom Flammulina velutipes. Following in vitro evaluation of functional activities, a few important findings were demonstrated. Mutants with reinforcing of N-terminal dimerization showed enhancement in its immunostimulatory and lung cancer A549 cell-inhibitory activities, presumably via increasing protein stability that led to prolong protein half-life. Mutations of loop DE and hinge residue E61K were crucial in directing immune response towards T helper 1 (TH1) and displayed significant inhibition towards breast cancer MDA-MB-231 cell viability, while mutations of loop FG and hinge residue I97D were important for inhibiting cell viability of A549 lung cancer cell and MCF-7 breast cancer cell. Loop DE adoption (LZ-8) also abolished haemagglutination ability of FIP-fve mutant, making it suitable for therapeutic use. The residues that are important in determining bioactivities of FIP-fve are tabled out. This study demonstrated for the first time that immunomodulatory and anti-cancer activities of FIP-fve can be enhanced via strengthened dimerization and loop modification. The research lays a foundation for other FIPs as immuno-therapeutic candidate in future.